2007
DOI: 10.1002/cphc.200600563
|View full text |Cite
|
Sign up to set email alerts
|

Ferric and Ferrous Iron in Nitroso‐Myoglobin: Computer Simulations of Stable and Metastable States and Their Infrared Spectra

Abstract: The binding of NO to iron is involved in the biological function of many heme proteins. Contrary to ligands like CO and O(2), which only bind to ferrous (Fe(II)) iron, NO binds to both ferrous and ferric (Fe(III)) iron. In a particular protein, the natural oxidation state can therefore be expected to be tailored to the required function. Herein, we present an ab initio potential-energy surface for ferric iron interacting with NO. This potential-energy surface exhibits three minima corresponding to eta(1)-NO co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 40 publications
1
21
1
Order By: Relevance
“…For rapid rebinding, p(d) has a broad maximum between 0.2 and 0.3 Å whereas for slower rebinding the maximum in p(d) shifts to 0.33 Å which agrees quite well with results from X-ray crystallography [166]. Apart from the previously considered relative orientation of the NO ligand to the heme-iron [150,152,153,158,167,168], the iron-out-of-plane (doming) coordinate will be explicitly considered. Recent time-resolved resonance Raman experiments suggested that the photodissociated ligand can rebind to the domed, Fe-out-of-plane conformation of the heme unit [156].…”
Section: International Reviews In Physical Chemistry 247supporting
confidence: 71%
See 3 more Smart Citations
“…For rapid rebinding, p(d) has a broad maximum between 0.2 and 0.3 Å whereas for slower rebinding the maximum in p(d) shifts to 0.33 Å which agrees quite well with results from X-ray crystallography [166]. Apart from the previously considered relative orientation of the NO ligand to the heme-iron [150,152,153,158,167,168], the iron-out-of-plane (doming) coordinate will be explicitly considered. Recent time-resolved resonance Raman experiments suggested that the photodissociated ligand can rebind to the domed, Fe-out-of-plane conformation of the heme unit [156].…”
Section: International Reviews In Physical Chemistry 247supporting
confidence: 71%
“…The Fe-ON minimum determined on the d ¼ À 0.2 Å surface located % 21.5 kcal/mol above the global Fe-NO minimum, is, however, shifted toward smaller values of (%120 ), with a geometry resembling more the metastable Fe-NO described previously [153]. Fe-NO transition is %3 kcal/mol.…”
Section: International Reviews In Physical Chemistry 247mentioning
confidence: 54%
See 2 more Smart Citations
“…39 This engenders interactions between the NO and the distal histidine in myoglobin that occur through a lone pair donation mechanism rather than a hydrogen bond leading to an upshift of the frequency. 45 In the case of substrate-free HRP, although a distal histidine residue is present in the active site, it has been shown to be more distant from the haem than would be required for direct interaction.…”
Section: Ftir Spectroscopymentioning
confidence: 99%